Workplace Peers and Entrepreneurship - Nanda, Ramana; Sørensen, Jesper B. (Management Science, 2010)
We examine whether the likelihood of entrepreneurial activity is related to the prior career experiences of an individual's coworkers, using a unique matched employer–employee panel data set. We argue that coworkers can increase the likelihood that an individual will perceive entrepreneurial opportunities as well as increase his or her motivation to pursue those opportunities. We find that an individual is more likely to become an entrepreneur if his or her coworkers have been entrepreneurs before. Peer influences also appear to be substitutes for other sources of entrepreneurial influence: we find that peer influences are strongest for those who have less exposure to entrepreneurship in other aspects of their lives.